The origin and early evolution of plants. (March 2023) - Bowles, Alexander M.C.; Williamson, Christopher J.; Williams, Tom A.; Lenton, Timothy M.; Donoghue, Philip C.J.
Abstract: Plant (archaeplastid) evolution has transformed the biosphere, but we are only now beginning to learn how this took place through comparative genomics, phylogenetics, and the fossil record. This has illuminated the phylogeny of Archaeplastida, Viridiplantae, and Streptophyta, and has resolved the evolution of key characters, genes, and genomes – revealing that many key innovations evolved long before the clades with which they have been casually associated. Molecular clock analyses estimate that Streptophyta and Viridiplantae emerged in the late Mesoproterozoic to late Neoproterozoic, whereas Archaeplastida emerged in the late-mid Palaeoproterozoic. Together, these insights inform on the coevolution of plants and the Earth system that transformed ecology and global biogeochemical cycles, increased weathering, and precipitated snowball Earth events, during which they would have been key to oxygen production and net primary productivity (NPP). Highlights: The origin of the first photosynthetic eukaryotes through to the first land plants transformed the Earth's biosphere. There is no single unified view of the processes and timing of early plant evolution despite myriad fossil and geochemical evidence. Phylogenetically targeted genomic, morphological, and Earth system data will be necessary to make significant advances in our understanding of early plant evolution given the deep timescales.